2022
DOI: 10.1186/s12909-022-03445-0
|View full text |Cite
|
Sign up to set email alerts
|

The nurse teacher’s pedagogical cooperation with students, the clinical learning environment and supervision in clinical practicum: a European cross-sectional study of graduating nursing students

Abstract: Background A supportive clinical practicum experience may enhance the successful transition and socialization to working life of graduating nursing students. Nurse teachers have the main responsibility of supporting and guiding nursing students with their pedagogical expertise during the students’ clinical practicum. Thus, the clinical role of nurse teachers is seen as an essential part of a high-quality clinical practicum. Nursing students appreciate the nurse teacher’s cooperation with studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The identified two‐factor model of the Tc2 scale may be used to obtain a broader understanding of the cooperation triad between the student, mentor and teacher and the actual implementation of the role of the teacher. “Cooperation triad” (factor 1) and “Teacher's pedagogical cooperation with students” (factor 2) are crucial in order to promote the effective learning and professional development of students during the clinical practicum (Hooven, 2014 ; Strandell‐Laine et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified two‐factor model of the Tc2 scale may be used to obtain a broader understanding of the cooperation triad between the student, mentor and teacher and the actual implementation of the role of the teacher. “Cooperation triad” (factor 1) and “Teacher's pedagogical cooperation with students” (factor 2) are crucial in order to promote the effective learning and professional development of students during the clinical practicum (Hooven, 2014 ; Strandell‐Laine et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the teacher bears the main responsibility for the student supervision (Directive 2005/36/EC ), and the cooperation triad has been the traditional part of the teacher's clinical role. Still, the role of the teacher has now changed with educational reforms from vocational education to higher educational institutions (Collins & Hewer, 2014 ; Strandell‐Laine et al, 2022 ). After the turn of the millennium, teachers’ clinical visits to practicum placements have decreased in Finland and throughout Europe (Saarikoski et al, 2013 ), mainly because of economic preconditions rather than pedagogical solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, students from six European countries valued the individualized supervision provided by their nurse teacher from the educational institute, as well as their support in enhancing learning and decreasing stress associated with clinical practicum [ 7 ]. Nevertheless, various studies have noted a general decline in the involvement of nurse teachers in clinical practice [ 6 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed negative perceptions among students regarding the clinical role of the nurse teacher [4,5,[10][11][12][13][14][15][16][17] probably due to these changes. To address this issue and improve nurse teacher's cooperation with students, studies highlight the need to develop novel alternative approaches, such as digital educational technologies [7,9,18], to complement rather than substitute the physical presence of nurse teachers during placements [18]. Furthermore, the nurse teacher's clinical role should be revised to include clear responsibilities for student supervision during clinical practicum [7], distinct from the responsibilities of clinical supervisors [9].…”
Section: Introductionmentioning
confidence: 99%